3(2y+6)=42

1 answer

To solve the equation \(3(2y+6)=42\), we can start by distributing the 3 on the left side:

\[ 3 \cdot 2y + 3 \cdot 6 = 42 \]

This simplifies to:

\[ 6y + 18 = 42 \]

Next, we want to isolate the term with \(y\). We can do this by subtracting 18 from both sides of the equation:

\[ 6y + 18 - 18 = 42 - 18 \]

This simplifies to:

\[ 6y = 24 \]

Now, to solve for \(y\), we divide both sides by 6:

\[ y = \frac{24}{6} \]

This gives us:

\[ y = 4 \]

So the solution is:

\[ \boxed{4} \]